PEMBASAHAN PADA LAHAN GAMBUT TERBAKAR DENGAN BERBAGAI SUMBER AIR TERHADAP PERUBAHAN SIFAT KIMIA TANAH (AgriPeat, 2020)
Land use and drainage canals cause irrevearsible drying, collapse in the dome, making fire easier. Efforts to prevent fires are wetting peatlands with water. The water sources that are often used by the community are rainwater, river water, ditch / canal water, and ground water / well water. This study aims to determine the effect of wetting from various water sources on changes in the chemical properties of inland peatlands, as well as to know the differences in the chemical properties of inland peatlands with different land uses. The study was conducted at the UPR Basic and Analytical Laboratory and soil sampling was carried out in Kalampangan Village, Sebangau District, Palangka Raya City. The study was conducted for 3 (three) months, from August to November 2019. The method used is a survey method and experimental test (in the field). The design used is a non-factorial complete randomized design (CRD) with the treatment of 4 AI sources (borehole water, river water, rain water, and channel / channel water). The parameters observed were soil chemical properties (pH, ash content, DHL (electrical conductivity), CEC, N-Total, available P, bases available, water content and Al saturation), and water chemistry (pH, DHL, and its cations and anions). The results showed that wetting using various sources of water on in-burned peat soils had no effect on changes in soil chemical properties. The highest pH and soil pH values ??were found in the treatment of soil wetting using well water / ground water at the 6th week with a pH value of 4.37 and the 4th week for DHL with a value of 163.33. The lowest soil pH and DHL values ??were at the 4th week rainwater treatment with a pH value of 3.48 and the 6th week at the DHL value of 35.33.